Usulan Penurunan Tingkat Kecacatan Produk Sosis Ayam di PT Charoen Pokphand Indonesia - -, Samuel; -, Felecia (Jurnal Titra, 2015)
PT Charoen Pokphand Indonesia is one of Indonesiaâs producer of poultry feed, day old chicks and processed chicken. This research is conducted in sausages plant in Surabaya which produced chicken and beef sausages. Chicken sausages have several types of defects like wrinkled (0,9%), fungus (0,04%), and reject cooking (0,34%). The purpose of this research is to find the defectâs root cause and to propose solutions to reduce chicken sausages defects.DMAIC is used as a method to find problemâs root cause and solution in this research along with interview and direct field observation. It is found that defects caused by operator lack of focus during operation, no quality inspection for PVDC plastic, machine breakdown and no standardized working procedure.This research proposed the company to give morning briefing for operators, quality inspection by quality control department for PVDC plastic, designing tray separator, designing checklist form, downtime form, and work instruction. It is expected to reduced chicken sausages defects up to 1,28%.